A Pedagogical Contribution of Digital Corpus-Based Instruction in ESP: Classroom Activities for Public Administration Students - Misnawati, Misnawati; Tahir, Saidna Zulfiqar Bin; Masriadi, Masriadi; Rahman, Abdul; Akifa, Nur; Krisnata, Arya (Innovations in Language Education and Literature, 2025)
This article makes a pedagogical contribution to English for Specific Purposes (ESP) by integrating Digital Corpus-based Instruction (DCI) model: Discovery (exploring authentic corpus data), Connection (engaging with QR-based multimedia resources), and Creation (producing meaningful texts through mobile-based tasks). Two classroom activities illustrate how the model can be applied for public administration students. The first activity (Unit 1: Public Administration Concepts) introduces key terms such as policy implementation, governance, and accountability. Students examine concordance lines from the Corpus of Contemporary American English (COCA), match them with expressions used in a video on good governance, and then write a short paragraph using the vocabulary learned. The second activity (Unit 2: Public Service and Bureaucracy) targets vocabulary such as public service, citizen satisfaction, and bureaucratic delay. Students analyze collocations from corpus data, compare them with language found in public service videos and audio recordings of citizen complaints, and then write a formal complaint letter applying these expressions. The findings suggest that corpus-based tasks raise students’ awareness of authentic language patterns and support the development of formal writing skills in ESP contexts. In addition, the DCI model offers a practical, adaptable framework that requires minimal resources, making it suitable for classroom implementation.